2014
DOI: 10.1111/codi.12491
|View full text |Cite
|
Sign up to set email alerts
|

To drain or not to drain extraperitoneal colorectal anastomosis? A systematic review and meta‐analysis

Abstract: The meta-analysis shows that the presence of a pelvic drain reduces the incidence of extraperitoneal colorectal anastomotic leakage and the rate of reintervention after anterior rectal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 33 publications
(63 reference statements)
0
47
0
2
Order By: Relevance
“…In particular, over the last 2 decades, a number of reports have suggested that routine drainage following rectal surgery might be unnecessary and possibly connected with increased morbidity [8-10, 14, 16]. Conversely, other experiences continue to favor the placement of drains on a routine basis [9-11]. Our meta-analysis suggests that prophylactic drainage does not confer any advantage in enhancing the surgical outcomes of patients receiving rectal surgery with extraperitoneal anastomosis.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…In particular, over the last 2 decades, a number of reports have suggested that routine drainage following rectal surgery might be unnecessary and possibly connected with increased morbidity [8-10, 14, 16]. Conversely, other experiences continue to favor the placement of drains on a routine basis [9-11]. Our meta-analysis suggests that prophylactic drainage does not confer any advantage in enhancing the surgical outcomes of patients receiving rectal surgery with extraperitoneal anastomosis.…”
Section: Discussionmentioning
confidence: 74%
“…The clinical value of prophylactically placed drains in colorectal surgery has been studied more frequently in comparison with other gastrointestinal surgeries and a general trend favoring a no-drainage policy has been observed [8, 9, 21-23]. In particular, over the last 2 decades, a number of reports have suggested that routine drainage following rectal surgery might be unnecessary and possibly connected with increased morbidity [8-10, 14, 16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations